1976
DOI: 10.1111/j.1476-5381.1976.tb07467.x
|View full text |Cite
|
Sign up to set email alerts
|

ANALYSIS OF THE EFFECTS OF p‐METHOXY‐PHENYLETHYLAMINE ON SPINAL CORD NEURONES

Abstract: I Para-methoxyphenylethylamine (PMPEA) was applied microiontophoretically onto interneurones and motoneurones in the spinal cords of acute spinal cats anaesthetized with a-chloralose. Its effects were compared with those of noradrenaline (NA) and 5-hydroxytryptamine (5-HT). 2 PMPEA had effects on interneurones which were similar to those of NA and/or 5-HT; its action was predominantly depressant, and it rarely affected interneurones which could not be influenced by NA or 5-HT. 3 The actions of PMPEA on interne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 19 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…An immunohistochemical study found on average, 4 serotonergic boutons on cat Renshaw cells (Carr et al 1999), confirming earlier reports that unlike for motoneurons, serotonin has a weak effect on Renshaw cells. Moreover, serotonin acts to inhibit Renshaw cells (Jordan and McCrea 1976). At present, voltage-gated channels have not been identified on the dendrites of Renshaw cells.…”
Section: Physiological Implicationsmentioning
confidence: 86%
“…An immunohistochemical study found on average, 4 serotonergic boutons on cat Renshaw cells (Carr et al 1999), confirming earlier reports that unlike for motoneurons, serotonin has a weak effect on Renshaw cells. Moreover, serotonin acts to inhibit Renshaw cells (Jordan and McCrea 1976). At present, voltage-gated channels have not been identified on the dendrites of Renshaw cells.…”
Section: Physiological Implicationsmentioning
confidence: 86%
“…For instance, aberrant sprouting of primary afferents or expansion of interneuronal receptive and projective fields after SCI may augment the excitatory drive to spinal networks [ 134 ]. On the other hand, inhibition is affected by the interruption of serotoninergic descending tracts, which modulate inhibitory interneurons, like Renshaw cells [ 135 , 136 ]. Moreover, Renshaw cell recurrent circuitry might become disconnected from motoneurons [ 137 ] suppressing their excitatory drive to Renshaw cells, in turn reducing the GABAergic inhibitory feedback.…”
Section: Fast Synaptic Gabaergic Transmission Is Early Affected By Spinal Cord Injurymentioning
confidence: 99%
“…Modulatory effects of monoamines on transmission between primary afferents and neurons in the mammalian spinal cord have been demonstrated for several neuronal populations, including various types of ascending tract neurons (Jordan et al, 1978, 1979); (Fleetwood‐Walker et al, 1985; Carlton et al, 1991; Jankowska et al, 1997a; Hammar et al, 2001) and interneurons, e.g. (Engberg and Ryall, 1965, 1966; Jordan and McCrea, 1976; Todd and Millar, 1983; Bras et al, 1989; Jankowska et al, 2000). Modulation of responses of individual functionally identified neurons of different populations by locally applied monoamines turned out to be highly differentiated, although the modulatory effects on neurons within a population have been relatively consistent.…”
mentioning
confidence: 99%